Interference Analysis of Postpaid kWh Meters According to Standard Operational Procedures at PT. PLN Ulp Helvetia Medan Indonesia: Analisis Gangguan Pada kWh Meter Pasca Bayar Menurut Standar Operasional Prosedur di PT. PLN Ulp Helvetia Medan Indonesia - Irgi Faturrahman; Soni Prayogi (Journal of Multidisciplinary Science, 2023)
In this work, we report that various electronic device are continuously being developed to support human life. The scale also varies, ranging from simple household appliances to heavy industrial equipment. In the process of collecting household electrical power, a kWh Meter is needed to simplify and minimize employee errors in inputting data on household and industrial electricity usage in the Medan City area. In its operation, operational and non-operational disturbances often occur such as congestion at the kWh meter, fire at the kWh meter, and other unavoidable disturbances. In overcoming disturbances that occur in kWh Meters, Inspection and Maintenance of kWh meters can be carried out, especially on digital / Postpaid kWh Meters. This report contains the type of kWh that is often used, the components in the kWh meter, the types of disturbances that often occur in the kWh meter, the impact on the damage to the kWh meter, and how to overcome these types of disturbances.